SERVQUAL ON SIM SERVICE AT TANJUNG BALAI POLICE STATION - Sri Maharani; Rizky Fauziah; Abdul Karim Syahputra (STMIK Royal, 2023)
Abstract : The demand for a driving license is increasing every year, making the Tanjungbalai Police, especially the Satlantas, continue to try to take new steps in the field of driving license processing services. To overcome this problem the researcher uses the Servqual Method, Service Quality There is a technique that assesses service quality based on the attributes of each dimension, producing a difference value that represents the difference between the customer's impression of the service it receives. The information used in this study's processing came from distributing it to 30 respondents who are members of the public who are currently obtaining a driver's license at the Tanjungbalai Traffic Traffic Unit. It is evident from this study's findings that satisfaction at Tanjungbalai Traffic Traffic Unit seen from the 5 dimensions of Servqual has a reality value of 4.00 an and expectation worth of 4.62 resulting in a void -0.62. This void occurs since cmmunity's expectations not being met with the services provided by the Tanjungbalai Traffic Unit for. Keywords-: service quality; service quality; tanjungbalai traffic police Abstrak-: Permintaan pembuatan surat izin mengemudi yang terus naik setiap saat tahunnya, menjadikan-Polres Tanjungbalai khususnya Satlantas pertahankan komitmen terhadap inovasi di sektor jasa pengurusan surat izin mengemudi. untuk mengatasi masalah tersebut peneliti menggunakan Metode Servqual, Service Quality yaitu teknik untuk mengevaluasi kualitas layanan berdasarkan kualitas masing-masing dimensi. Hasil akhirnya yaitu nilai kesenjangan, yang merepresentasikan variasi dalam cara pelanggan memandang layanan yang mereka terima. Informasi yang digunakan dalam pengolahan penelitian ini berasal dari rilis data ke 30 responden yang sedang melakukan pengurusan Surat Izin Mengemudi pada Satlantas Tanjungbalai. Dari hasil penelitian ini terlihat bahwa kepuasan masyarakat di Satlantas Tanjungbalai dilihat dari lima dimensi servqual yaitu didapatkan jumlah nilai kenyataan sebesar 4,00 kemudian jumlah 4,62 lalu-gap -0,62. Gap-perbedaan hasil dari harapan yang tidak terpenuhi masyarakat terhadap pelayanan pada Satlantas Tanjungbalai. Kata kunci: kualitas pelayanan; service quality; satlantas tanjungbalai